THE FEASIBILITY, IMPACT, AND RECOMENDATION FOR THE ISSUANCE OF CENTRAL BANK DIGITAL CURRENCY - jaroenphol, atikan (Huachiew Chalermprakiet Law Journal, 2024)
Payment in Thailand has begun from using coins and banknotes to electronic payment. One of the key technologies is distributed processing technology, which allows service users on the same network to exchange information, including transactions between them, without going through intermediaries. The Bank of Thailand has developed the Inthanon project to test the potential and feasibility of applying this technology to Thailand’s payment system, including issuing digital currency issued by the Central Bank, but with the development of the national financial sector, the Currency act b.e.2501 was issued on August 18, 1958, and it is still valid today. The act may not be consistent with current economic and social conditions. Therefore, to be able to understand more about central bank-issued digital currencies, including to be able to present the feasibility, impact, and recommendations for the issuance of a central bank digital currency. The author therefore conducted a study Gather information about Central Bank Digital Currency.